The Influence of Peer Groups on the Islamic Personality of Female Students at the State Islamic University of Madura - Siti Fatima; Abd Mannan (Tarbiyah Wa Ta'lim: Jurnal Penelitian Pendidikan dan Pembelajaran, 2026)
Abstract This study aims to analyze the relationship and contribution of peer groups to the formation of Islamic personality (syakhshiyah Islamiyah) among female students at Universitas Islam Negeri (UIN) Madura. Islamic personality is formed through the integration of Islamic thinking patterns (aqliyah Islamiyah) and Islamic behavioral patterns (nafsiyah Islamiyah). The research problem is based on the phenomenon that although peer groups on an Islamic campus have a religious atmosphere, the Islamic personality of female students has not been fully, completely, and consistently. The research uses a quantitative approach with a correlational method. The respondents were female students of the Faculty of Tarbiyah from the 2022–2025 cohorts at Universitas Islam Negeri Madura. Data analysis techniques included correlation testing and simple regression analysis. The analysis results indicate a positive correlation between peer groups and Islamic personality, with a correlation coefficient of 0.405, which falls into the moderate category. However, the coefficient of determination (R2) value of 0.164 shows that peer groups contribute only 16.4% to the formation of Islamic personality. This finding indicates that peer groups have a positive influence on Islamic personality, although their contribution is relatively limited. Keywords: female students, islamic personality, peer groups.